2008
DOI: 10.1016/j.ijid.2008.05.228
|View full text |Cite
|
Sign up to set email alerts
|

HCV Genotypes in Haemodialysis Units: A Preliminary Study

Abstract: Background: Human enterovirus 71 (HEV71) is a common aetiology of hand-foot-and-mouth-disease (HFMD) where it occasionally causes CNS illnesses. In 1997, Sarawak experienced a HEV71-associated HFMD outbreak with 34 deaths reported. Following the outbreak, a prospective HFMD surveillance study showed that HE71-associated HFMD outbreaks occurred in Sarawak every three years, each caused predominantly by different genogroups of HEV71; genogroup-B3 in 1997, genogroup-B4 in 2000, and genogroup-B5 in 2003 This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A limited number of articles were found in the surveyed scientific literature that looked into the biodynamics of HCV infection in general and in HD patients in particular. [1][2][3][4][5][6][7][8] Fabrizi et al 7 studied the biological dynamics of viral load in patients infected with hepatitis C virus associated with end-stage renal diseases who were undergoing maintenance haemodialysis, where the serum HCV RNA was measured monthly for 13 months using branched DNA signal amplification assay. He found that larger fluctuations in HCV RNA levels occurred in patients with persistent than in those with intermittent HCV viraemia.…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of articles were found in the surveyed scientific literature that looked into the biodynamics of HCV infection in general and in HD patients in particular. [1][2][3][4][5][6][7][8] Fabrizi et al 7 studied the biological dynamics of viral load in patients infected with hepatitis C virus associated with end-stage renal diseases who were undergoing maintenance haemodialysis, where the serum HCV RNA was measured monthly for 13 months using branched DNA signal amplification assay. He found that larger fluctuations in HCV RNA levels occurred in patients with persistent than in those with intermittent HCV viraemia.…”
Section: Introductionmentioning
confidence: 99%